Die Zeit der Regionen im Spiegel der Gebelein-Region : kulturgeschichtliche Re-konstruktionen - Morenz, Ludwig D. (Probleme der Ägyptologie, 2010)
Egyptian historiography is determined by the fact that transmission of the historical record is left to chance. Ludwig Morenz therefore develops a method of "fragmentarily thick description," borrowing terminology from anthropologist Clifford Geertz, as a way of addressing the holes left in the record while still arriving at as complete a picture of the third century BCE Gebelein society as possible. From this localized perspective, a new understanding of the region's culture, including conceptualizations of the landscape, the socio-economic situation, the mentality of the people and their methods of discourse, arises. Even with this new method the private realities of the men, women, and children can remain in shadows. However, it is possible, as a result of the descriptive model, to better understand the sources at hand and to draw connections among intellectual-, economic-, and social-historical frameworks. Utilizing Morenz's method widens our understanding of the traditionally undervalued "dark" times of the third century BCE Gebelein region. Upon closer examination of the socio-economic and mentalities history, the transformation of Egyptian society emerges as colorful and contradictory.